A coupled BEM-ALEM approach for analysis of elastic thin plates on multilayered soil with anisotropic permeability. (April 2015) - Ai, Zhi Yong; Hu, Ya Dong
Abstract: In this article, a coupled BEM-ALEM approach is presented to analyze the elastic thin plates resting on saturated poroelastic multilayered soil with anisotropic permeability. The direct boundary element method is applied to dissect the rectangular thin plate based on the Kirchhoff assumption. And the analytical layer-element method (ALEM) is used to derive the stiffness matrix of saturated poroelastic multilayered soil with anisotropic permeability. By introducing the conditions of displacement harmony at the interface between the plate and soil, the stiffness matrix of soil is directly incorporated into the developed BEM formulation of the plate. Moreover, the effect of the plate-soil relative stiffness and stratification of soil system on the time-dependent behavior of the plate situated on saturated poroelastic multilayered soil is analyzed.